Income of the Local Public Treasury in Mexico - Zúñiga-Espinoza, Nicolás Guadalupe; Reyes Perez, Narce Dalia (Technium Social Sciences Journal, 2022)
Own income for the local public treasury in Mexico must be more productive. One of its main characteristics is that in 2018 they financed 23 cents of each peso that was spent at the municipal level; while transfers contributed with 73 cents. On the other hand, the public debt contributed with 4 cents to the public spending of municipal governments. However, it was observed that property tax is not being well used, so it can generate more benefits if it is put to work in favor of providing quality public goods and services for the residents who live in the municipal space. Under the current fiscal coordination scheme, transfers will continue to be the most important resource for this level of government, but it is necessary that the level of property tax collection reaches at least one point of GDP for the next decade.